Self-repairing fluoride red fluorescent powder and preparation method thereof
By forming a double inorganic protective layer on the surface of Mn4+-doped fluoride red phosphor, the problem of its poor chemical stability in a humid environment is solved, and the luminescence performance is improved and the self-repair ability is achieved, making it suitable for high color rendering lighting and wide color gamut display LEDs.
Patent Information
- Application Number
- CN202510960516.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-09-09
AI Technical Summary
Mn4+-doped fluoride red phosphors have poor chemical stability in humid environments, resulting in reduced luminescence performance, and existing surface modification methods cannot provide long-term protection.
It adopts K2MF6:Mn4+ core, coated with manganese-free passivation layer K2MF6 and composite protective layer NSO3/NSO4, and forms a double inorganic protective layer through the reaction of sulfite and water-soluble salt solution. The outer layer contains a coating layer of sulfite ion groups to achieve self-repair function.
The moisture and heat resistance of the phosphor are improved, the luminescence performance and thermal stability are enhanced, and the luminescence performance is maintained without degradation during storage or service, and it has self-repair ability.
Smart Images

Figure CN120607886A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of luminescent materials, and in particular relates to a self-repairing fluoride red phosphor and a preparation method thereof. Background Art
[0002] In recent years, Mn 4+ Fluoride-doped red phosphors have important application value in high color rendering lighting and wide color gamut display LEDs. Compared with rare earth elements, Mn elements are abundant in reserves and have low preparation costs. 4+ It is one of the few commercially used phosphors. However, the chemical stability of fluoride red phosphor is poor. In a humid environment, the activator Mn 4+ It is easily hydrolyzed into its hydroxide or oxide, and the luminescence performance will be greatly reduced or even lose the luminescence ability.
[0003] To solve the problem of Mn 4+ The stability of fluoride-doped red phosphors in ultra-humid environments is mostly studied by modifying the phosphor surface to form a protective layer, so that Mn 4+ Isolate from water and oxygen to avoid hydrolysis and deterioration. According to the differences and similarities between the surface modified protective layer and the internal phosphor material, it can be divided into heterogeneous surface coating and homogeneous surface passivation. Heterogeneous surface coating can be carried out by organic coating with octadecyltrimethoxysilane (ODTMS), oleic acid, oleylamine (OAm), etc., or inorganic coating with CaF2, Al2O3, K2SiF6, etc. Homogeneous surface passivation refers to the use of a supersaturated solution to reversely perform ion exchange or reduction surface passivation, or a combination of the two, to generate a manganese-poor or manganese-free passivation layer. However, both heterogeneous surface coating and homogeneous surface passivation can only slow down the rate of phosphor deterioration. During storage or service, the luminescence performance of the phosphor will continue to decrease, and it cannot play a long-term in-situ protection role. Summary of the Invention
[0004] In view of this, an object of the present invention is to provide a self-repairing fluoride red phosphor and a preparation method thereof.
[0005] In the first aspect, the present invention provides a self-repairing fluoride red phosphor, the chemical formula of which is K2MF6:Mn 4 + @K2MF6@NSO3 / NSO4, where: M is one of Si, Ti, and Ge, and N is one of Ba, Ca, and Sr; specifically, K2MF6:Mn 4 + The core, the manganese-free passivation layer K2MF6 coated on the core, and NSO3 and NSO4 coated on the manganese-free passivation layer constitute a composite protective layer.
[0006] In a second aspect, the present invention provides a method for preparing a self-repairing fluoride red phosphor, comprising the following steps: K2MF6:Mn 4+ The self-repairing fluoride red phosphor is dispersed in a solvent to obtain a dispersion; an aqueous solution of sulfite and / or sulfurous acid is added to the dispersion to carry out a stirring reaction; after the reaction is completed, a water-soluble salt solution of N is added to the reaction liquid to carry out a second stirring reaction; after the reaction is completed, the self-repairing fluoride red phosphor is obtained by centrifugation.
[0007] Preferably, the solvent is one or more of ethanol, methanol, acetone, and acetic acid; K2MF6:Mn 4+ The mass volume ratio to the solvent is (0.4~0.6)g / (2~3)mL.
[0008] Preferably, the sulfite is a water-soluble sulfite, specifically one or more of sodium sulfite, ammonium sulfite, and potassium sulfite; the concentration of the aqueous solution of sulfite and / or sulfurous acid is 0.01-5.0 mol / L.
[0009] Preferably, K2MF6:Mn 4+ The mass ratio of sulfite and / or sulfurous acid is (0.4~0.6):(0.05~0.15).
[0010] Preferably, the stirring reaction time is 20 to 120 minutes.
[0011] Preferably, the water-soluble salt of N is one or more of N chloride and N nitrate; The concentration of the water-soluble salt solution of N is 0.01~5.0mol / L.
[0012] Preferably, the molar ratio of sulfite in the aqueous solution of sulfite and / or sulfurous acid to N metal ions in the aqueous solution of N is 8:(1.5-8), more preferably 8:(4.8-8).
[0013] Preferably, the second stirring reaction time is 20 to 120 minutes.
[0014] Preferably, the precipitate after centrifugation is washed with acetic acid and anhydrous ethanol in sequence, and the washed precipitate is vacuum dried to obtain a self-repairing fluoride red phosphor.
[0015] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: (1) The self-repairing fluoride red phosphor in the present invention has a double inorganic protective layer. The inner layer of the protective layer is a manganese-free homogeneous passivation layer of the phosphor, and the outer layer is a coating layer containing sulfite ion groups. Compared with the single-layer protective layer or organic protective layer of general technology, it has stronger moisture and heat resistance, and the luminescence performance and thermal stability of the phosphor are improved.
[0016] (2) Due to the presence of the reducing coating layer, the self-repairing fluoride red phosphor of the present invention has a certain self-repairing ability. During storage or service, the luminescence performance of the phosphor will not only not decrease, but will also be improved to a certain extent, which can provide continuous protection for the phosphor.
[0017] (3) The preparation process of the self-repairing fluoride red phosphor in the present invention does not reduce the luminescence performance, the method is relatively simple, and it is easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 These are scanning electron microscope images of the phosphors prepared in Example 1 and Preparation Example 1, respectively; (a) Preparation Example 1, (b) Example 1.
[0019] Figure 2 The XRD spectra of the phosphors prepared in Example 1 and Preparation Example 1 are respectively.
[0020] Figure 3 These are the excitation spectra and emission spectra of the phosphors prepared in Example 1 and Preparation Example 1, respectively.
[0021] Figure 4 Graphs showing relative integrated intensities of the excitation spectra of the phosphors prepared in Example 1 and Preparation Example 1, respectively.
[0022] Figure 5 Graphs showing relative integrated intensities of emission spectra of the phosphors prepared in Example 1 and Preparation Example 1 after being immersed for different times.
[0023] Figure 6 Graphs showing relative integrated intensity results of emission spectra of the phosphors prepared in Example 1 and Preparation Example 1 at different temperatures. DETAILED DESCRIPTION
[0024] To facilitate understanding of the present invention, the present invention will be described in more comprehensive and detailed form below in conjunction with the accompanying drawings and preferred embodiments. However, the protection scope of the present invention is not limited to the following specific embodiments. Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0025] As mentioned above, in the first aspect, the present invention provides a self-repairing fluoride red phosphor, the chemical formula of which is K2MF6:Mn 4+ @K2MF6@NSO3 / NSO4, where: M is one of Si, Ti, and Ge, and N is one of Ba, Ca, and Sr; specifically, K2MF6:Mn 4+ The core, the manganese-free passivation layer K2MF6 coated on the core, and NSO3 and NSO4 coated on the manganese-free passivation layer constitute a composite protective layer.
[0026] The self-healing fluoride red phosphor of this invention features a dual inorganic protective layer, which offers enhanced moisture and heat resistance compared to conventional single-layer and organic protective layers. This improves both the phosphor's luminescence performance and thermal stability. Furthermore, because the outer coating is reducing, it continuously releases sulfite ions, enabling self-healing through an in-situ reaction and providing continuous protection.
[0027] In addition, the outer protective layer of the double inorganic protective layer of the self-repairing fluoride red phosphor in the present invention is a composite protective layer composed of NSO3 and NSO4. NSO4 can improve the stability of NSO3, thereby achieving a better self-repairing effect.
[0028] In a second aspect, the present invention provides a method for preparing a self-repairing fluoride red phosphor, comprising the following steps: K2MF6:Mn 4+ The self-repairing fluoride red phosphor is dispersed in a solvent to obtain a dispersion; an aqueous solution of sulfite and / or sulfurous acid is added to the dispersion to carry out a stirring reaction; after the reaction is completed, a water-soluble salt solution of N is added to the reaction liquid to carry out a second stirring reaction; after the reaction is completed, the self-repairing fluoride red phosphor is obtained by centrifugation.
[0029] The present invention uses one or more of sulfurous acid and / or sulfite salts as a reducing agent to perform surface reduction passivation to form a manganese-free homogeneous inorganic passivation layer. Water-soluble N salts can combine with sulfite ions to form an insoluble precipitate, solidifying the reducing sulfite ion groups on the phosphor surface. A reducing inorganic coating layer is further formed on top of the homogeneous inorganic passivation layer, forming a double inorganic protective layer. The present invention utilizes inexpensive raw materials, a simple preparation method, is environmentally friendly, and is easily scalable for industrial production.
[0030] The method of the present invention is to prepare the outermost protective layer by precipitation method, K2MF6:Mn 4+@K2MF6 dispersed in the solvent can act as a crystal nucleus. Therefore, the water-soluble salt solution of N preferentially combines with sulfite and / or sulfate ions and coats the phosphor surface. There are almost no free small particle precipitates, which has little impact on the phosphor morphology and does not affect the performance of the phosphor.
[0031] Preferably, the solvent is one or more of ethanol, methanol, acetone, and acetic acid; K2MF6:Mn 4+ The mass volume ratio to the solvent is (0.4~0.6)g / (2~3)mL.
[0032] Preferably, the sulfite is a water-soluble sulfite, specifically one or more of sodium sulfite, ammonium sulfite, and potassium sulfite; the concentration of the aqueous solution of sulfite and / or sulfurous acid is 0.01-5.0 mol / L.
[0033] Preferably, K2MF6:Mn 4+ The mass ratio of sulfite and / or sulfurous acid is (0.4~0.6):(0.05~0.15).
[0034] Preferably, the stirring reaction time is 20 to 120 minutes.
[0035] Preferably, the water-soluble salt of N is one or more of N chloride and N nitrate; The concentration of the water-soluble salt solution of N is 0.01~5.0mol / L.
[0036] Preferably, the molar ratio of sulfite in the aqueous solution of sulfite and / or sulfurous acid to N metal ions in the aqueous solution of N is 8:(1.5-8), more preferably 8:(4.8-8).
[0037] Preferably, the second stirring reaction time is 20 to 120 minutes.
[0038] Preferably, the precipitate after centrifugation is washed with acetic acid and anhydrous ethanol in sequence, and the washed precipitate is vacuum dried to obtain a self-repairing fluoride red phosphor.
[0039] K2SiF6:Mn used in the present invention 4+ The specific preparation method can be seen in Preparation Example 1; K2TiF6:Mn 4+ It was purchased directly.
[0040] Preparation Example 1K2SiF6:Mn 4+ Synthesis of phosphors K2MnF6 was synthesized according to the Bode method: 5g KHF2 and 0.4g KMnO4 were completely dissolved in 10mL HF (HF concentration was 40wt%), and then 0.4mL H2O2 was slowly added dropwise to the purple-black solution under vigorous stirring; when the solution color turned light yellow, it was allowed to stand and then centrifuged. The solid product was washed with acetic acid and anhydrous ethanol in turn, and finally dried at 70°C for 4h to obtain K2MnF6.
[0041] K2SiF6:Mn 4+ Synthesis of phosphor: 0.3226 g K2MnF6 was added to a plastic beaker containing 22.5 mL HF, stirred thoroughly to dissolve, and then 18.75 mL HF solution containing 0.875 g SiO2 (HF concentration was 40 wt%) was added. After stirring thoroughly for 10 min, 12.5 mL HF solution containing 3.5 g KHF2 (HF concentration was 40 wt%) was added to the mixed solution. After stirring thoroughly for 30 min, the mixture was centrifuged. The solid product was washed with acetic acid and anhydrous ethanol in turn, and then dried at 70 ° C for 5 h to obtain K2SiF6:Mn 4+ Phosphor.
[0042] Example 1 The chemical formula of the self-repairing phosphor prepared in this embodiment is: K2SiF6:Mn 4+ @K2SiF6@BaSO3 / BaSO4; the specific preparation method is as follows: 0.5g K2SiF6:Mn 4+ (Preparation Example 1) was placed in a centrifuge tube, and then 2.5 mL of anhydrous ethanol was added and stirred for 5 minutes. Then, 1 mL of 0.8 mol / L Na2SO3 solution was added and stirred for 30 minutes. Then, 0.8 mL of 0.8 mol / L BaCl2 solution was added to the mixed solution and stirred for 30 minutes. The mixture was centrifuged, and the solid product was washed with acetic acid and anhydrous ethanol in sequence to obtain a precipitate. The obtained precipitate was dried in a vacuum drying oven at 70°C for 5 hours to obtain K2SiF6:Mn 4+ @K2SiF6@BaSO3 / BaSO4 phosphor.
[0043] Performance testing: (1) Micromorphology test: The K2SiF6:Mn 4+ Phosphor and K2SiF6:Mn prepared in Example 1 4+ @K2SiF6@BaSO3 / BaSO4 phosphor was observed by scanning electron microscopy, and the results are as follows Figure 1 shown. Figure 1 a in K2SiF6:Mn4+ The particles of phosphor are square in structure. Figure 1 K2SiF6:Mn in b 4+ @K2SiF6@BaSO3 / BaSO4 phosphor also has a square structure, but the surface of the square structure is covered with a coating layer, indicating that the reaction process does not change the structure of the phosphor particles and has little effect on the morphology of the phosphor. In addition, no independent large BaSO3 / BaSO4 particles were observed, indicating that BaSO3 / BaSO4 is preferentially deposited on the K2SiF6:Mn 4+ surface.
[0044] (2) XRD test The K2SiF6:Mn 4+ Phosphor and K2SiF6:Mn prepared in Example 1 4+ @K2SiF6@BaSO3 / BaSO4 phosphor was tested by XRD, and the results can be seen Figure 2 , it can be seen that the K2SiF6:Mn 4+ Phosphors are consistent with the standard card (PDF#75-0694); K2SiF6:Mn prepared in Example 1 4+ @K2SiF6@BaSO3 / BaSO4 phosphor also matches the standard card (PDF#75-0694) and no other peaks appear, which may be due to the K2SiF6:Mn 4+ After reduction passivation and reductive inorganic coating treatment, the content of elements (Ba, S, O) in the surface reductive inorganic coating layer is low and its composition cannot be detected by XRD.
[0045] (3) Excitation spectrum and emission spectrum test The K2SiF6:Mn 4+ Phosphor and K2SiF6:Mn prepared in Example 1 4+ @K2SiF6@BaSO3 / BaSO4 phosphor was tested for excitation spectrum and emission spectrum, and the results can be seen Figure 3 and Figure 4 ; It can be seen that Figure 3 In Example 1, K2SiF6:Mn 4+ After the phosphor is coated, its excitation spectrum and emission spectrum are better than those of K2SiF6:Mn in Preparation Example 1. 4+ The phosphor intensity is higher, indicating that the K2SiF6:Mn 4+ @K2SiF6@BaSO3 / BaSO4 phosphor powder is more sparse than K2SiF6:Mn in Preparation Example 1 4+ Phosphor has better performance; and Figure 4The relative integrated intensity results show that K2SiF6:Mn 4+ The integrated intensity of @K2SiF6@BaSO3 / BaSO4 phosphor is the K2SiF6:Mn 4+ The integrated intensity of the phosphor is 106%, so after double-layer inorganic coating treatment, the luminescence performance of the phosphor can be effectively improved.
[0046] (4) Moisture resistance test 0.3 g of K2SiF6:Mn 4+ Phosphor and 0.3g K2SiF6:Mn prepared in Example 1 4+ @K2SiF6@BaSO3 / BaSO4 phosphors were placed in 2 mL of deionized water, and the relative integrated intensity of the emission spectra of the phosphors was tested after the phosphors were immersed for 30 min, 60 min, 120 min, 180 min, and 240 min. The test data can be seen in Tables 1 and Figure 5 It can be seen that the K2SiF6:Mn 4+ In the first 30 minutes, the relative integrated intensity of the phosphor decreases very quickly; while the K2SiF6:Mn 4+ The relative integrated intensity of @K2SiF6@BaSO3 / BaSO4 phosphor powder not only did not decrease in the first 60 minutes, but also increased; and remained relatively stable from 60 to 240 minutes. 4+ @K2SiF6@BaSO3 / BaSO4 phosphor can achieve in-situ self-repair to enhance luminescence in a humid environment, which can effectively solve the storage problem of phosphor in an environment with high humidity and provide long-term protection.
[0047] Table 1 The relative integrated intensity in the table is based on the corresponding initial phosphor (before immersion) as a reference.
[0048] (5) Heat resistance test The K2SiF6:Mn 4+ Phosphor and K2SiF6:Mn prepared in Example 1 4+ The emission spectra of @K2SiF6@BaSO3 / BaSO4 phosphor were tested at 25℃, 50℃, 75℃, 100℃, 125℃, 150℃, 175℃ and 200℃ respectively. The relative integrated intensities can be seen in Table 2 and Figure 6 It can be seen that K2SiF6:Mn in Preparation Example 1 4+Phosphor and K2SiF6:Mn prepared in Example 1 4+ @K2SiF6@BaSO3 / BaSO4 phosphors all reach their maximum relative integrated intensity at 150°C, with the maximum relative integrated intensity of the phosphor of Example 1 being 107% and that of the phosphor of Preparation Example 1 being 105%. At 200°C, they reach their minimum relative integrated intensity, with the relative integrated intensity of the phosphor of Example 1 being 93% and that of the phosphor of Preparation Example 1 being 88%. This indicates that K2SiF6:Mn 4+ After double-layer inorganic coating treatment, its thermal stability is improved to a certain extent.
[0049] Table 2 The relative integrated intensities in the table are based on the fluorescence intensity of the corresponding phosphors at 25°C.
[0050] Comparative Example 1 The chemical formula of the phosphor prepared in this comparative example is: K2SiF6:Mn 4+ @K2SiF6; the specific preparation method is as follows: 0.5g K2SiF6:Mn 4+ (Preparation Example 1) was placed in a centrifuge tube, and then 2.5 mL of anhydrous ethanol was added and stirred for 5 minutes. Then, 1 mL of 0.8 mol / L Na2SO3 solution was added and stirred for 30 minutes. The mixture was centrifuged, and the solid product was washed with acetic acid and anhydrous ethanol in sequence to obtain a precipitate. The obtained precipitate was dried in a vacuum drying oven at 70°C for 5 hours to obtain K2SiF6:Mn 4+ @K2SiF6 phosphor.
[0051] Comparative Example 2 The chemical formula of the self-repairing phosphor prepared in this comparative example is: K2SiF6:Mn 4+ @K2SiF6@BaSO4; the specific preparation method is as follows: 0.5g K2SiF6:Mn 4+(Preparation Example 1) was placed in a centrifuge tube, and then 2.5 mL of anhydrous ethanol was added and stirred for 5 minutes, and then 1 mL of 0.8 mol / L Na2SO3 solution was added and stirred for 30 minutes, and then centrifuged. The solid product was washed with acetic acid and anhydrous ethanol in sequence to obtain a precipitate; 2.5 mL of anhydrous ethanol was added to the precipitate and stirred for 5 minutes, and then 0.8 mL of 0.8 mol / L Na2SO4 solution was added and stirred for 30 minutes, and then 0.8 mL of 0.8 mol / L BaCl2 solution was added to the mixed solution, stirred for 30 minutes, and centrifuged. The solid product was washed with acetic acid and anhydrous ethanol in sequence to obtain a secondary precipitate, and the secondary precipitate was dried in a vacuum drying oven at 70°C for 5 hours to obtain K2SiF6:Mn 4+ @K2SiF6@BaSO4 phosphor.
[0052] The phosphors in Comparative Examples 1 and 2 were tested for performance according to the moisture resistance test method described in Example 1. The results are shown in Table 3. Compared to the phosphor in Preparation Example 1, the moisture resistance of the phosphors in Comparative Examples 1 and 2 was somewhat improved. However, the moisture resistance of the phosphor in Comparative Example 2 was not superior to that of Comparative Example 1. This may be because the two coating layers of K₂SiF₆ and BaSO₄ did not synergize, but instead degraded the phosphors, resulting in a decrease in moisture resistance. The moisture resistance of Comparative Examples 1 and 2 was significantly lower than that of Example 1, indicating that moisture resistance can only be effectively improved when the outer coating layer is a composite of BaSO₃ / BaSO₄.
[0053] Table 3 The relative integrated intensity in the table is based on the corresponding initial phosphor (before immersion) as a reference.
[0054] Example 2 This example is basically the same as Example 1, except that the volume ratio of BaCl2 added is different. This example includes multiple groups of parallel experiments, as shown in Table 4.
[0055] Table 4 The K2SiF6:Mn prepared by adding different volumes of BaCl2 in Example 2 4+ The relative integrated intensity of the emission spectrum of @K2SiF6@BaSO3 / BaSO4 phosphor is shown in Table 5. It can be seen that K2SiF6:Mn 4+The performance of @K2SiF6@BaSO3 / BaSO4 phosphor first increases and then decreases with the increase of BaCl2 addition. This may be because if there is too little Ba salt, the BaSO3 / BaSO4 coating layer plays a limited role. If there is too much Ba salt, BaSO3 / BaSO4 may produce larger precipitated particles, which will affect the performance of the phosphor.
[0056] Table 5 The relative integrated intensity in the table is based on the K2SiF6:Mn 4+ Phosphor was used as a reference.
[0057] Example 3 The chemical formula of the self-repairing phosphor prepared in this embodiment is: K2TiF6:Mn 4+ @K2TiF6@CaSO3 / CaSO4; the specific preparation method is as follows: 0.6g K2TiF6:Mn 4+ (Preparation Example 1) was placed in a centrifuge tube, and then 3.0 mL of acetone was added and stirred for 5 minutes. Then, 0.2 mL of 5 mol / L (NH4)2SO3 solution was added and stirred for 120 minutes. Then, 2 mL of 0.1 mol / L CaCl2 solution was added to the mixed solution and stirred for 120 minutes. The mixture was centrifuged, and the solid product was washed with acetic acid and anhydrous ethanol in sequence to obtain a precipitate. The obtained precipitate was dried in a vacuum drying oven at 70°C for 5 hours to obtain K2TiF6:Mn 4+ @K2TiF6@CaSO3 / CaSO4 phosphor.
[0058] K2TiF6:Mn 4+ The phosphor in this embodiment was tested for moisture resistance and heat resistance according to the test method in Example 1. The results can be seen in Tables 6 and 7.
[0059] From the data in Table 6 and Table 7, it can be seen that the moisture resistance and heat resistance of the phosphor in Example 3 are better than those of K2TiF6:Mn 4+ Both have been improved to a certain extent and show similar self-repair phenomena.
[0060] Table 6 Moisture resistance The relative integrated intensity in the table is based on the corresponding initial phosphor (before immersion) as a reference.
[0061] Table 7 Heat resistance The relative integrated intensity in the table is based on the fluorescence intensity of the respective phosphors at 25°C as a reference.
[0062] Example 4 The chemical formula of the self-repairing phosphor prepared in this embodiment is: K2TiF6:Mn 4+ @K2TiF6@BaSO3 / BaSO4; the specific preparation method is as follows: 0.4g K2TiF6:Mn 4+ (Preparation Example 1) was placed in a centrifuge tube, and then 2.0 mL of methanol was added and stirred for 5 minutes, followed by the addition of 10 mL of 0.1 mol / L Na2SO3 solution and thorough stirring for 20 minutes. Then, 0.1 mL of 5 mol / L Ba(NO3)2 solution was added to the mixed solution and stirred for 20 minutes. The mixture was then centrifuged, and the solid product was washed with acetic acid and anhydrous ethanol in sequence to obtain a precipitate. The obtained precipitate was dried in a vacuum drying oven at 70°C for 5 hours to obtain K2TiF6:Mn 4+ @K2TiF6@BaSO3 / BaSO4 phosphor.
[0063] The phosphor in this example was tested for moisture resistance and heat resistance according to the test method in Example 1. The results can be seen in Tables 8 and 9.
[0064] From the data in Table 8 and Table 9, it can be seen that the moisture resistance and heat resistance of the phosphor in Example 4 are better than those of K2TiF6:Mn 4+ Both have been improved to a certain extent and show similar self-repair phenomena.
[0065] Table 8 Moisture resistance The relative integrated intensity in the table is based on the initial phosphor (before immersion) as a reference.
[0066] Table 9 Heat resistance The relative integrated intensity in the table is based on the fluorescence intensity of the phosphor at 25°C.
[0067] The above embodiments are intended only to illustrate the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent changes or modifications made in accordance with the spirit of the present invention are intended to be covered by the scope of protection of the present invention.
Claims
1. A self-repairing fluoride red phosphor, characterized in that: The chemical formula of the phosphor is K2MF6:Mn 4+ @K2MF6@NSO3 / NSO4, where: M is one of Si, Ti, and Ge, and N is one of Ba, Ca, and Sr; specifically, K2MF6:Mn 4+ The core is coated with a manganese-free passivation layer K2MF6, and the manganese-free passivation layer is coated with NSO3 and NSO4 to form a composite protective layer.
2. A method for preparing the self-repairing fluoride red phosphor according to claim 1, comprising the following steps: K2MF6:Mn 4+ The self-repairing fluoride red phosphor is dispersed in a solvent to obtain a dispersion; an aqueous solution of sulfite and / or sulfurous acid is added to the dispersion to carry out a stirring reaction; after the reaction is completed, a water-soluble salt solution of N is added to the reaction liquid to carry out a second stirring reaction; after the reaction is completed, the self-repairing fluoride red phosphor is obtained by centrifugation.
3. The method for preparing the self-repairing fluoride red phosphor according to claim 2, characterized in that: The solvent is one or more of ethanol, methanol, acetone, and acetic acid; K2MF6:Mn 4+ The mass volume ratio of the solvent is (0.4~0.6)g:(2~3)mL.
4. The method for preparing the self-repairing fluoride red phosphor according to claim 2, wherein: The sulfite is a water-soluble sulfite, specifically one or more of sodium sulfite, ammonium sulfite, and potassium sulfite.
5. The method for preparing the self-repairing fluoride red phosphor according to claim 2 or 4, characterized in that: K2MF6:Mn 4+ The mass ratio of sulfite and / or sulfurous acid is (0.4~0.6):(0.05~0.15).
6. The method for preparing the self-repairing fluoride red phosphor according to claim 2, characterized in that: The stirring reaction time is 20 to 120 minutes; the second stirring reaction time is 20 to 120 minutes.
7. The method for preparing the self-repairing fluoride red phosphor according to claim 2, characterized in that: The water-soluble salt of N is one or more of N chloride and N nitrate.
8. The method for preparing the self-repairing fluoride red phosphor according to claim 2, 4 or 7, wherein: The concentration of the aqueous solution of sulfite and / or sulfurous acid is 0.01-5.0 mol / L, and the concentration of the water-soluble salt solution of N is 0.01-5.0 mol / L; the molar ratio of sulfite ions in the aqueous solution of sulfite and / or sulfurous acid to N metal ions in the water-soluble salt solution of N is 8:(1.5-8).
9. The method for preparing the self-repairing fluoride red phosphor according to claim 8, characterized in that: The molar ratio of sulfite in the aqueous solution of sulfite and / or sulfurous acid to N metal ion in the water-soluble salt solution of N is 8:(4.8~8).
10. The method for preparing the self-repairing fluoride red phosphor according to claim 2, characterized in that: The precipitate after centrifugation is washed with acetic acid and anhydrous ethanol in sequence, and the washed precipitate is vacuum dried to obtain a self-repairing fluoride red phosphor.